Who sank the boat? - Allen, Pamela (London : Puffin, 1982)
The reader is invited to guess who causes the boat to sink when five animal friends of varying sizes decide to go for a row.
Keywords: Animals -- Fiction; Boats and boating -- Fiction; Animals -- Fiction; Boats and boating -- Fiction